Comparison of Multilocus Sequence Typing and Spa Typing of Staphylococcus aureus Isolated from Bovine and Bubaline Mastitis - Sheela, Purushottam; Isloor, Shrikrishna; Rathnamma, Doddamane; Veeregowda, Belamaranahally; Sundareshan, Srinivasaiah; R Hegde, Nagendra (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Staphylococcus aureus (S. aureus) is the leading causative agent of mastitis in dairy cows, causing reduced milk quality and production. The present study describes the genotypes and clonal distributions of 35 S. aureus strains isolated from cases of mastitis from southern India by multi-locus sequence typing (MLST). The resultant S. aureus sequence types (STs) were compared with their Staphylococcus protein A (spa) types and correlated to methicillin resistance. A total of 27 methicillin-sensitive Staphylococcus aureus (MSSA) and eight methicillin-resistant Staphylococcus aureus (MRSA) strains were identified. Twenty different STs with nine new alleles and nine new STs were obtained. The STs were grouped into four clonal complexes (CCs) CC1, CC5, CC8 and CC97. The predominant STs 2454 and 2459 belonged to CC8 and CC97, respectively. Eight STs were not clustered under any of the CCs. Comparison of genotypes of MLST with that of spa types revealed that some of the isolates with same ST yielded different spa types that were closely related to each other. On the contrary, some of the isolates with same spa types gave different STs in which one ST was the single locus variant of the other in all the cases. Overall, high diversity of S. aureus isolates was observed, excepting for the isolates from a particular geographical region (Bidar) in Karnataka.